Stochastic frontier analysis in higher education: A systematic review - Sabine Gralka (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2018)
This paper provides a systematic review of the literature that employs stochastic frontier analysis to measure the efficiency of higher education institutions. The overview opens with a look at the general development of the literature, before emphasis is laid on the methodical aspects. Focus is thereby placed on the necessary underlying assumptions and the employed specifications, discussing their advantages and drawbacks. Afterwards, the factors that were specified in the literature, including the input and output variables, as well as the determinants of efficiency, are discussed in detail. Based on the insights of the literature review, the paper highlights some of the existing deficiencies and ways forward. To our knowledge, the present study provides the first systematic review on the usage of the stochastic frontier analysis to measure efficiency in the higher education sector.
urn:nbn:de:bsz:14-qucosa2-324599
Keywords: C14; D61; I22; I23; H52; 330; Review; Efficiency; Higher Education; Stochastic Frontier Analysis